2002
DOI: 10.1097/00004694-200209000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The charts and radiographs of 79 patients with osteogenesis imperfecta (OI) actively followed at the authors' institution were reviewed to determine the incidence of acetabular protrusion (AP) in OI and to evaluate the clinical consequences of this pelvic deformity. All 79 patients had iliac crest bone biopsy and pelvic radiographs. They were subdivided into OI type 1, 3, and 4, according to the Sillence classification, and type 5, according to Glorieux. AP was measured on pelvic radiographs, using the center-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Acetabular protrusio has been reported in 33% to 55% of the patients with OI and in an estimated 70% of the patients specifically with type 3 OI. 5 , 6 Although intuition suggests a correlation between acetabular protrusio and constipation, the limited data available have been inconsistent; Violas et al found that only 8% of patients with acetabular protrusio reported symptoms of constipation, whereas Lee et al demonstrated an increased risk of chronic constipation and recurrent abdominal pain in the presence of acetabular protrusio. 3 , 5 No published studies exist that seek to assess the relationship between pelvic deformity and severity of constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Acetabular protrusio has been reported in 33% to 55% of the patients with OI and in an estimated 70% of the patients specifically with type 3 OI. 5 , 6 Although intuition suggests a correlation between acetabular protrusio and constipation, the limited data available have been inconsistent; Violas et al found that only 8% of patients with acetabular protrusio reported symptoms of constipation, whereas Lee et al demonstrated an increased risk of chronic constipation and recurrent abdominal pain in the presence of acetabular protrusio. 3 , 5 No published studies exist that seek to assess the relationship between pelvic deformity and severity of constipation.…”
Section: Discussionmentioning
confidence: 99%
“…The manifestations of this disease in the musculoskeletal system vary 1 2) . The OI hip often has a varus deformity as well as “pincer” type impingement because of the acetabular protrusio 3 4 5) . With the resulting excessive forces on the femoral neck by the impingement, a “stress” fracture of the femoral neck can develop.…”
mentioning
confidence: 99%